THE ROLE OF SPA INDUSTRY VISITS IN IMPROVING THE WORK READINESS OF VOCATIONAL EDUCATION STUDENTS: A LITERATURE STUDY - Esty Nuria Ayu Ningsih; Nia Kusstianti; Novia Restu Windayani (Universitas Negeri Surabaya, 2025)
Job readiness is a key indicator of the effectiveness of vocational education in preparing graduates to meet the demands of industry. One form of industry engagement that contributes to enhancing students’ job readiness is industrial visits, particularly in the beauty and spa sector, which requires technical competence and professional work attitudes. This study aims to systematically examine the role of industrial visits in improving job readiness among vocational education students using a Systematic Literature Review (SLR) approach guided by the PRISMA framework. The literature search was conducted through Google Scholar and nationally accredited (SINTA-indexed) journals, yielding 45 articles at the initial identification stage. Following the screening and eligibility assessment processes, 18 articles met the inclusion criteria and were analyzed further. The findings indicate that industry-oriented learning, experiential learning, teaching factory models, industrial work practice, internships, and industrial visits significantly contribute to vocational students’ job readiness. Industrial visits function as an initial exposure to real workplace environments, work culture, and industry standards, thereby strengthening students’ mental readiness, professional attitudes, and contextual understanding of the world of work. In the context of vocational education in the beauty and spa field, industrial visits represent an integral component of industry-based learning that helps bridge the gap between school-based instruction and industry practice.